Toward a Theory of Organizational Creativity - Woodman, Richard W.; Sawyer, John E.; Griffin, Ricky W. (Academy of Management Review, 1993)
Your use of the JSTOR archive indicates your acceptance of JSTOR's Terms and Conditions of Use, available at